1976
DOI: 10.1021/bi00656a030
|View full text |Cite
|
Sign up to set email alerts
|

A calorimetric study of the thermotropic behavior of aqueous dispersions of natural and synthetic sphingomyelins

Abstract: A recently developed differential scanning calorimeter has been used to characterize the thermotropic behavior of aqueous dispersions of liposomes containing sphingomyelin. Liposomes derived from sheep brain sphingomyelin exhibit a broad gel-liquid crystalline phase transition in the temperature range of 20-45 degrees C. The transition is characterized by maxima in the heat capacity function at 31.2 and 37.1 degrees C and a total enthalpy change of 7.2 +/-0.4 kcal/mol. Beef brain sphingomyelin liposomes behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
97
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(110 citation statements)
references
References 20 publications
12
97
1
Order By: Relevance
“…5 shows normalized emission spectra of laurdan in BBSM-containing SUV. According to differential scanning calorimetry, BBSM undergoes a broad chain melting transition around 37°C (32). The emission maxima reflect not only the ordered and fluid states of the bilayer (23 and 45°C, respectively) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 shows normalized emission spectra of laurdan in BBSM-containing SUV. According to differential scanning calorimetry, BBSM undergoes a broad chain melting transition around 37°C (32). The emission maxima reflect not only the ordered and fluid states of the bilayer (23 and 45°C, respectively) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 show that the protein is also insoluble when it is in liposomes containing lipids in the gel phase. Lipids with high T m , such as sphingolipids, can form a gel phase at or near physiological temperatures (30). Alternatively, they can form an l o phase in the presence of cholesterol (13).…”
Section: Cholesterol Is Not Required For Detergent Resistance Of Plapmentioning
confidence: 99%
“…This effect was attributed to the more heterogeneous mixture of acyl chains found with natural lipid systems and would likely lessen the order of l o domains when compared with l o domains formed from synthetic lipids (Jin et al, 2006). Similarly, a calorimetric study by Barenholz et al (1976) examined the thermotropic behavior of lipid vesicles composed of natural and synthetic sphingomyelin lipid species. It was reported that membrane organization of sphingomyelin is a complex function of its specific composition and that the transition temperature of natural sphingomyelin was much broader than the synthetic forms.…”
Section: Resultsmentioning
confidence: 99%